Delineating the dispersal of Y-chromosome sub-haplogroup O2a2b-P164 among Austronesian-speaking populations - Javier Rodriguez Luis; Leire Palencia-Madrid; Göran Runfeldt; Ralph Garcia-Bertrand; Rene J. Herrera (Scientific Reports, 2024)
Abstract This article reports on an exploration of the Y-chromosome sub-haplogroup O2a2b-P164 in Austronesian-speaking populations. Moderate to high abundance of the P 164 mutation is seen in the West Pacific including the Amis of Formosa (36%) and the Filipinos of Mindanao (50%) as well as in the Kiritimati of Micronesia (70%), and Tonga and Samoa of West Polynesia (54% and 33%, respectively), and it drops to low frequencies in populations of East Polynesia. The communities of Polynesia and Micronesia exhibit considerable inter- and intra-population haplotype sharing suggesting extensive population affinity. The observed affinities, as well as the ages and diversity values within the P 164 sub-haplogroup among Austronesian-speaking populations signal an ancestral migration route and relationships that link the Amis of Taiwan with distant communities in West and East Polynesia, Micronesia, and the Maori of New Zealand. High resolution sequencing of the Austronesian Y chromosome indicate that the P 164 lineage originated about 19,000 ya and then split into three branches separating the Ami aborigines, Southeast Asian and Polynesian/Micronesian populations about 4700 ya, roughly coinciding with the initiation of the Austronesian diaspora. The Y-chromosomes of all the Polynesian and Micronesian population examined belong to the new FT 257096 haplogroup.